Avian vision and egg colouration: concepts and measurements. (20th December 2011) - Stevens, Martin
Avian egg colours and patterns are spectacularly diverse and provide a wonderful system to study both the functional and mechanistic basis of animal colouration. In order to do this, it is essential to consider the vision of the appropriate receiver, particularly birds, and to use methods and models to quantify the colour patterns independent of subjective human assessment. In this paper, I summarise some of the key features of avian colour, luminance, and pattern vision, and provide an outline of the methods available to quantify visual signals, including their associated benefits and limitations. In doing so, I make links to various recent studies of avian eggshell colouration, and a range of other relevant studies. Overall, I argue that considering receiver vision and employing appropriate methods to quantify eggshell appearance is crucial to understanding the basis of avian egg diversity.